Inhibition of Colony Stimulating Factor 1 Receptor Suppresses Neuroinflammation and Neonatal Hypoxic-Ischemic Brain Injury - Zhang, Bohao; Ran, Yunwei; Wu, Siting; Zhang, Fang; Huang, Huachen; Zhu, Changlian; Zhang, Shusheng; Zhang, Xiaoan (Frontiers in Neurology, 2021)
Hypoxic-ischemic (HI) brain injury is a major cause of neonatal death or lifetime disability without widely accepted effective pharmacological treatments. It has been shown that the survival of microglia requires colony-stimulating factor 1 receptor (CSF1R) signaling and microglia participate in neonatal HI brain injury. We therefore hypothesize that microglia depletion during a HI insult period could reduce immature brain injury. In this study, CD1 mouse pups were treated with a CSF1R inhibitor (PLX3397, 25 mg/kg/daily) or a vehicle from postnatal day 4 to day 11 (P4–11), and over 90% of total brain microglia were deleted at P9. Unilateral hemisphere HI injury was induced at P9 by permanently ligating the left common carotid arteries and exposing the pups to 10% oxygen for 30 min to produce moderate left hemisphere injury. We found that the PLX3397 treatment reduced HI brain injury by 46.4%, as evaluated by the percentage of brain infarction at 48 h after HI. Furthermore, CSF1R inhibition suppressed the infiltration of neutrophils (69.7% reduction, p = 0.038), macrophages (77.4% reduction, p = 0.009), and T cells (72.9% reduction, p = 0.008) to the brain, the production of cytokines and chemokines (such as CCL12, CCL6, CCL21, CCL22, CCL19, IL7, CD14, and WISP-1), and reduced neuronal apoptosis as indicated by active caspase-3 labeled cells at 48 h after HI (615.20 ± 156.84/mm2 vs. 1,205.00 ± 99.15/mm2, p = 0.013). Our results suggest that CSF1R inhibition suppresses neuroinflammation and neonatal brain injury after acute cerebral hypoxia-ischemia in neonatal mice.